Perlindungan Hukum Terhadap Jurnalis Korban Tindak Pidana Kekerasan Dalam Menjalankan Tugas Jurnalistik Di Kota Kupang - Tulle, Kevin Christian; Manuain, Orpa G; Dede, Ngongo (Artemis Law Journal, 2025)
The persecution experienced by journalists is one of the crimes, the persecution of journalists is intended for legal protection of journalists from acts in the form of attacks on body parts or other parts that cause injury, even death. In Kupang City, several cases of persecution of the Press also occurred so widespread, one of the cases was "The attempted murder of one of the journalists and the Editor-in-Chief (Pemred) of Suara Flobamora who was investigating and reporting on alleged corruption in the Regional Company PT. Flobamor, became a momentum for Law Enforcement Officers in the NTT Region (Kejati NTT and Polda NTT and KPK) to pay serious attention, namely to respond by immediately conducting an investigation into alleged corruption. This adds to the dark record of legal protection related to criminal acts against the press or journalists and clearly requires quick action in tackling and mitigating this. The problems that will be studied in this study are as follows: (1) How is the legal protection for journalists who are victims of violent crimes in carrying out journalistic duties optimal? (2) How are efforts to optimize legal protection for journalists who are victims of violent crimes in carrying out journalistic duties in Kupang City?